Elderly Service Officer Trainings - Wernigg, Róbert; Kisdi, Réka; Tróbert, Anett Mária; Patyán, László (Magyar Gerontológia, 2020)
Introduction One of the challenges that stands before the aging population is the integration and mental and physical wellbeing of the elderly, and building the culture of active ageing. Meeting this challenge requires the activity of professionals who, in alliance with the work and services of the local governments, will become able to organise programmes that meet the needs and demands of the older citizens. This objective is targeted by the Elderly Service Officer Trainings provided by Family-Friendly Country Public Beneficiary Ltd. Methods: Our goal is to enable future Elderly Service Officers to actively contribute and enforce lawful practice to preparing, organising and implementing local civil programmes that target active aging; to recognise the special needs of the older citizens; and to orient within the legal environment of the programmes for the elderly. They should become able to co-operate efficiently with local government officials and NGOs supporting active ageing. Training topics: 1. Active ageing and mental wellbeing, 2. Community development, networking, volunteering, 3. Environment for active ageing, 4. Planning and implementing elderly friendly programmes. As regards to monitoring effectiveness, above activity indicators, we survey the changes of attitudes among trainees, and further activities of the Elderly Service Officers. The effectiveness studies are in progress. Results: Since May 2019, 16 study groups with 238 attendees have been launched (11 in Budapest és 5 on the countryside), and 12 groups have finished, yielding 144 certified trainees. We are planning a further set of 23 groups for 2021, in order to achieve the planned number of participants of 1000. Discussion: Further development of the training will depend on our future results. Supported by: Grant No. EFOP-1.2.6-VEKOP-17-2017-00001, „Family Friendly Country Project. References: L Patyán, JI Tóth, AM Tróbert, R Wernigg: Methodology to Aid the Community Inclusion and Person-Centered Care of Older Generations. Family-Friendly Country Public Beneficiary Ltd., 2019.